Value Addition of non-timber forest products and other tribal products - Rohini, A; Selvi, M Padma; Anjugam, M (Indian Farming, 2017)
Imparting training, providing market intelligence, establishing linkages with financial institutions, providing managerial inputs is the need of the hour for the livelihood development of tribal population who depend on NTFPs and other minor forest products.